Development of Departmental Statistical Accounting of the Federal Penitentiary Service in the Conditions of Digital Transformation - O. V. Soboleva (Статистика и экономика, 2022)
The purpose of the study is to analyze the existing departmental statistical accounting of the Federal Penitentiary Service and to form approaches to its development in the context of modern transformations associated with the use of digital technologies.Materials and methods: the peculiarities of the organization of the information resource and departmental statistical accounting of the Federal Penitentiary Service are analyzed, their shortcomings that prevent the integration of departmental statistics with other information resources of the department are identified, the main directions of digital transformation of departmental statistical accounting are highlighted, technological solutions for the implementation of the main processes are proposed, guidelines for the digital transformation of departmental statistics are formulated. In this paper, the author applied methods of theoretical study of control systems in the form of analysis and synthesis, modeling, empirical research - in the form of comparison and observation. Results. The transition of state bodies to the digital environment should include not only the automation of processes, but also the introduction of a process approach to management. End-to-end automation of work processes in the Federal Penitentiary Service is ensured by the introduction of a unified information system. The core task of the integration of information resources belongs to statistics, a data mart that is a supplier of open ordered data in the department and for interdepartmental exchange, will be formed on its basis. A necessary direction for the development of the established practice of collecting, processing and analyzing information is the use of its various sources for statistical purposes on the principles of their methodological and technological compatibility. The demand for statistical information will be the basis for the production of statistical products.Conclusion. The material outlines the contours of a modern model of departmental statistical accounting, capable of adapting to the requirements of consumers. Accounting is based on the primary missing link, which creates the prerequisites for reliable statistics. This type of accounting is designed for solving management problems, creation of favorable conditions for all interested users to navigate in the digital space, to understand the logic of working with data and to use them in their daily practical activities.